Using our Classroom Walls: A Project for Visualizing the Development of Conceptual Understanding. Issue 3 (16th March 2018) - Mayes-Tang, Sarah
Abstract: Practices such as making connections between topics, prioritizing content, and identifying broad themes are essential to learning mathematics. This paper describes a project designed to integrate these synthesizing activities into an abstract algebra class. Students used a classroom wall to record and organize their collective learning and developing knowledge, with an emphasis on visual connections. The evolution of the wall reflected the development of students' thinking throughout the course, and helped to personalize the classroom space. Suggestions for implementing similar projects in different courses and spaces are also included.